Asphalt composite additive with warm mixing and odor removing functions
By using a composite additive composed of polyethylene, polyvinyl acetate, modified nano-activated carbon, and calcium stearate, the problem of insufficient odor neutralization ability of warm mix asphalt additives is solved, achieving low-temperature construction and effective odor neutralization while maintaining the road performance of asphalt.
Patent Information
- Application Number
- CN202511329329.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-17
- Publication Date
- 2025-12-02
AI Technical Summary
Existing warm mix asphalt additives lack odor neutralization capabilities, and odor neutralizers affect the warm mix performance of asphalt, failing to effectively reduce the emission of harmful fumes.
A composite additive composed of polyethylene, polyvinyl acetate, modified nano-activated carbon, and calcium stearate is used. The modified nano-activated carbon is loaded with copper oxide, manganese oxide, and cerium oxide to catalyze the decomposition of harmful molecules. The nano-activated carbon adsorbs uncatalyzed harmful gases. The silane coupling agent improves compatibility. Maleic anhydride grafted onto polyethylene increases compatibility. Calcium stearate assists in uniform dispersion.
It achieves the fluidity and workability of asphalt at lower temperatures, while significantly reducing the emission of harmful gases and ensuring that the performance of asphalt for road use is not affected.
Smart Images

Figure BDA0005600677000000071 
Figure BDA0005600677000000081 
Figure BDA0005600677000000082
Abstract
Description
Technical Field
[0001] This invention relates to the field of road engineering materials technology, specifically to an asphalt composite additive that combines warm mixing and odor removal functions. Background Technology
[0002] With the continuous development of highway transportation construction, the performance of asphalt mixtures in road engineering is receiving increasing attention. Asphalt is a mixture mainly composed of elements such as carbon, hydrogen, sulfur, and oxygen. Asphalt mixtures are made by mixing mineral aggregates with asphalt binders. Depending on the construction temperature, asphalt mixtures are often divided into hot-mix asphalt and warm-mix asphalt. Hot-mix asphalt typically requires heating the asphalt mixture to 160-180℃ to make it fluid before construction. Warm-mix asphalt mainly uses additives to reduce the viscosity and construction temperature of the asphalt, allowing the asphalt mixture to have good fluidity at lower temperatures. Its construction temperature is usually 40-60℃ lower than that of hot-mix asphalt. Warm-mix asphalt not only maintains the road performance of asphalt but also significantly reduces carbon emissions. However, both hot-mix and warm-mix asphalt emit harmful fumes during storage, transportation, and use, causing pollution to construction workers and the environment, and even causing symptoms such as headaches, nausea, and coma.
[0003] Although there have been numerous studies on warm mix asphalt and asphalt neutralizers, current warm mix additives often lack neutralizing ability, while the effect of neutralizers on removing harmful fumes from asphalt needs to be further improved, and neutralizers may also affect the warm mix performance of asphalt. Summary of the Invention
[0004] In view of this, the present invention provides an asphalt composite additive that combines warm mixing and odor removal functions. This composite additive can not only reduce the viscosity of asphalt mixtures to achieve warm mixing construction, but also has an odor removal function, which greatly reduces the release of harmful gases and odors from asphalt, and does not affect the basic properties of asphalt.
[0005] To solve the above technical problems, the first aspect of the present invention provides an asphalt composite additive with both warm mixing and deodorizing functions, comprising, by weight: 50-60 parts of polyethylene, 30-45 parts of polyvinyl acetate, 20-30 parts of maleic anhydride-grafted polyethylene, 35-50 parts of modified nano-activated carbon, and 15-25 parts of calcium stearate; wherein the modified nano-activated carbon is loaded with metal oxides and silane coupling agents, and the metal oxides are a mixture of copper oxide, manganese oxide, and cerium oxide.
[0006] The asphalt composite additive provided by this invention has both warm mixing and deodorizing functions. It uses polyethylene and polyvinyl acetate as non-polar and polar components, respectively, so that the composite additive can achieve good compatibility with asphalt and reduce the viscosity of asphalt as much as possible. It has better fluidity than asphalt without the composite additive, thereby achieving the conditions for construction at lower temperatures. The modified nano-activated carbon used is loaded with a mixture of copper oxide, manganese oxide, and cerium oxide, along with a silane coupling agent. On one hand, the three elements synergistically form a "catalytic center," which can catalyze the decomposition of harmful molecules such as phenols and thiols released from asphalt during heating into carbon dioxide and water, fundamentally reducing the presence of harmful substances. On the other hand, the multi-level porous structure of the nano-activated carbon itself can adsorb uncatalyzed harmful gases released from asphalt, inhibiting the escape of harmful fumes. The presence of the silane coupling agent not only ensures good compatibility between the nano-activated carbon and the asphalt matrix but also utilizes its good compatibility with the asphalt matrix and the chemical bonding between it and metal oxides (the silanol end of the silane coupling agent forms covalent bonds with the hydroxyl groups generated by the metal oxides on the surface of the nano-activated carbon to achieve connection), thus "pulling" the nano-activated carbon apart and solving the problem of easy agglomeration. Maleic anhydride-grafted polyethylene, as a dispersant, can increase the compatibility between polyethylene, polyvinyl acetate, modified nano-activated carbon, and the asphalt matrix, ensuring the warm-mixing and deodorizing effect of the composite additive after being added to asphalt. Calcium stearate acts as a lubricant, helping the composite additives to disperse evenly in the asphalt matrix.
[0007] In conjunction with the first aspect, the loading rate of the metal oxide on the surface of the nano-activated carbon is 20%-28%. This loading rate ensures that the modified nano-activated carbon surface has sufficient catalytic sites without affecting the pore structure of the activated carbon itself, thus ensuring that the composite additive has a good deodorizing effect.
[0008] Preferably, the loading rate of the metal oxide on the surface of the nano-activated carbon is 23%-25%.
[0009] In conjunction with the first aspect, the specific surface area of the nano-activated carbon is 1000-2000 m². 2 / g, preferably 1300-1600m 2 / g.
[0010] In conjunction with the first aspect, the preparation method of the modified nano-activated carbon is as follows:
[0011] Nano-activated carbon is dispersed in an acidic solution and stirred at 70-80℃ for 3-4 hours to obtain an activated slurry;
[0012] The pH of the activated slurry was adjusted to 7.5-9, and soluble metal salts of copper, manganese and cerium were added. The mixture was stirred and reacted at 60-70℃ under ultrasonic conditions for 10-12 hours. After solid-liquid separation, the obtained solid was washed and calcined at 400-450℃ under inert conditions for 1-2 hours to obtain metallized nano-activated carbon.
[0013] The metallized nano-activated carbon was dispersed in an alcohol solution containing a silane coupling agent and stirred at 40-50°C for 4-6 hours. After solid-liquid separation, the mixture was dried to obtain the modified nano-activated carbon.
[0014] First, the nano-activated carbon is activated in an acidic solution, then adsorbs soluble metal salts under weakly alkaline conditions. After high-temperature calcination, the metal salts are converted into corresponding metal oxides. Then, a silane coupling agent is loaded to increase the compatibility of the modified nano-activated carbon with other polymer matrix raw materials, so that the modified nano-activated carbon has both catalytic and adsorption effects.
[0015] In conjunction with the first aspect, the amount of the soluble metal salt added is 40%-80% of the mass of the nano-activated carbon.
[0016] In conjunction with the first aspect, the soluble metal salts of copper, manganese and cerium are the corresponding nitrates or chlorides.
[0017] In conjunction with the first aspect, in the soluble metal salts of copper, manganese and cerium, the mass ratio of copper salt, manganese salt and cerium salt is 1:2-3:0.5-0.8 respectively.
[0018] Preferably, the soluble metal salts of copper, manganese and cerium are a mixture in which the mass ratio of copper salt, manganese salt and cerium salt is 1:2.5:0.6.
[0019] Preferably, the acidic solution can be an aqueous solution of nitric acid or hydrochloric acid; the silane coupling agent can be selected from any one of KH550, KH560 or KH570.
[0020] A second aspect of this invention provides a method for preparing the above-mentioned asphalt composite additive that combines warm mixing and odor-reducing functions, comprising the following steps:
[0021] The modified nano-activated carbon, a portion of maleic anhydride-grafted polyethylene, and a portion of calcium stearate were added to a high-speed mixer in proportion and mixed for 5-10 minutes to obtain a premix.
[0022] The polyethylene, polyvinyl acetate, the balance of maleic anhydride-grafted polyethylene, and the balance of calcium stearate are mixed together with the premix and then mixed in a high-speed mixer for 10-15 minutes to obtain the mixture.
[0023] The mixture is sequentially heated and melted, then extruded and granulated to obtain the asphalt composite additive that combines warm mixing and odor removal functions.
[0024] By pre-mixing modified nano-activated carbon with a portion of maleic anhydride-grafted polyethylene and a portion of calcium stearate, and then mixing polyethylene, polyvinyl acetate, the remaining maleic anhydride-grafted polyethylene and the remaining calcium stearate with the premix, it is possible to ensure that the modified nano-activated carbon is uniformly distributed in the polymer matrix and avoid agglomeration during the preparation process; then, it is obtained by heating, melting and extrusion granulation.
[0025] In conjunction with the second aspect, the process of heating, melting, extruding, and granulating specifically involves heating the mixture to 160-180°C in a twin-screw extruder for 3-5 minutes, setting the screw speed to 300-400 rpm, and then extruding and granulating it.
[0026] A third aspect of the present invention provides a warm-mix asphalt comprising the above-mentioned asphalt composite additive with both warm-mix and deodorizing functions, or an asphalt composite additive with both warm-mix and deodorizing functions prepared according to the above-mentioned preparation method.
[0027] In conjunction with the third aspect, the composite additive accounts for 1%-2.5% of the mass of warm-mix asphalt.
[0028] The beneficial effects of this invention are as follows:
[0029] The asphalt composite additive provided by this invention combines warm-mix and odor-reducing functions. Through specific selection of the formula composition, a composite additive with both warm-mix and odor-reducing functions is obtained. When this composite additive is added to asphalt, it not only does not affect the asphalt's road performance and processing properties, but also reduces the asphalt mixing temperature by 25-40℃, allowing paving to be achieved at 100-110℃ and compaction at 90-100℃. Moreover, in addition to fixing harmful gases inside the asphalt through adsorption, this composite additive can also reduce the escape of harmful gases by catalytically decomposing the harmful gases released during the hot mixing process, thus producing a "double insurance" effect. Detailed Implementation
[0030] To make the objectives, technical solutions, and advantages of this invention clearer, the invention will be further described in detail below with reference to specific embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the invention and are not intended to limit the invention.
[0031] It will be understood by those skilled in the art that, unless otherwise defined, all terms used herein (including technical and scientific terms) have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. It should also be understood that terms such as those defined in general dictionaries should be understood to have the meaning consistent with their meaning in the context of the prior art, and should not be interpreted in an idealized or overly formal sense unless specifically defined.
[0032] Unless otherwise specified, the instruments, equipment and chemical reagents used in the following embodiments and comparative examples of this invention are all commercially available products.
[0033] It should be noted that the modified nano-activated carbon used in the following examples was prepared according to the following method: 100 parts by mass of nano-activated carbon (specific surface area 1300-1500 m²) was used. 2 / g) is dispersed in an aqueous nitric acid solution with a pH of 2-3, heated to 70-80℃ and stirred for 3-4 hours to obtain an activated slurry with an activated surface. The pH of the activated slurry is adjusted to 7.5-9 with sodium hydroxide solution and ammonia water, and 55 parts of soluble metal salt (12 parts of anhydrous copper nitrate, 35 parts of anhydrous manganese nitrate, and 8 parts of anhydrous cerium nitrate) are added. The mixture is stirred at 60-70℃ for 10-12 hours under ultrasonic frequency of 300Hz. After the reaction, the mixture is filtered, the solid collected is washed with water, and calcined at 400-450℃ for 1-2 hours under nitrogen protection to obtain metallized nano-activated carbon. All the metallized nano-activated carbon is added to an ethanol solution with a concentration of 10%-15% of silane coupling agent KH570, and stirred at 40-50℃ for 4-6 hours. After the reaction, the mixture is filtered to obtain modified nano-activated carbon.
[0034] Tests showed that the loading rate of metal oxides in the modified nano-activated carbon prepared by the above method was 23.2%.
[0035] Example 1
[0036] This embodiment provides an asphalt composite additive with both warm-mixing and odor-neutralizing functions. By weight, it comprises: 55 parts polyethylene, 40 parts polyvinyl acetate, 25 parts maleic anhydride-grafted polyethylene, 40 parts modified nano-activated carbon, and 20 parts calcium stearate. Its preparation method is as follows:
[0037] 40 parts of modified nano-activated carbon, 10 parts of maleic anhydride-grafted polyethylene, and 8 parts of calcium stearate were added to a high-speed mixer and mixed at 800 rpm for 8 minutes to obtain a premix. 55 parts of polyethylene, 40 parts of polyvinyl acetate, 15 parts of maleic anhydride-grafted polyethylene, and 12 parts of calcium stearate were mixed together with the premix and mixed in a high-speed mixer for 12 minutes to obtain a mixture. The mixture was added to a twin-screw extruder and heated to 170°C for melt blending for 3 minutes (screw speed 350 rpm). After that, it was extruded and granulated to obtain granular asphalt composite additives with warm mixing and deodorizing functions.
[0038] Example 2
[0039] This embodiment provides an asphalt composite additive with both warm-mixing and odor-neutralizing functions. By weight, it comprises: 50 parts polyethylene, 30 parts polyvinyl acetate, 20 parts maleic anhydride-grafted polyethylene, 35 parts modified nano-activated carbon, and 15 parts calcium stearate. Its preparation method is as follows:
[0040] 35 parts of modified nano-activated carbon, 8 parts of maleic anhydride-grafted polyethylene, and 5 parts of calcium stearate were added to a high-speed mixer and mixed at 800 rpm for 5 minutes to obtain a premix. 50 parts of polyethylene, 30 parts of polyvinyl acetate, 12 parts of maleic anhydride-grafted polyethylene, and 10 parts of calcium stearate were mixed together with the premix and mixed in a high-speed mixer for 10 minutes to obtain a mixture. The mixture was added to a twin-screw extruder and heated to 160°C for melt blending for 4.5 minutes (screw speed 350 rpm). After that, it was extruded and granulated to obtain granular asphalt composite additives with both warm mixing and deodorizing functions.
[0041] Example 3
[0042] This embodiment provides an asphalt composite additive with both warm-mixing and odor-neutralizing functions. By weight, it comprises: 60 parts polyethylene, 45 parts polyvinyl acetate, 30 parts maleic anhydride-grafted polyethylene, 50 parts modified nano-activated carbon, and 25 parts calcium stearate. Its preparation method is as follows:
[0043] 50 parts of modified nano-activated carbon, 15 parts of maleic anhydride-grafted polyethylene, and 12 parts of calcium stearate were added to a high-speed mixer and mixed at 800 rpm for 10 minutes to obtain a premix. 60 parts of polyethylene, 45 parts of polyvinyl acetate, 15 parts of maleic anhydride-grafted polyethylene, and 13 parts of calcium stearate were mixed together with the premix and mixed in a high-speed mixer for another 15 minutes to obtain a mixture. The mixture was added to a twin-screw extruder and heated to 180°C for melt blending for 3 minutes (screw speed 350 rpm). After extrusion and granulation, granular asphalt composite additives with warm mixing and deodorizing functions were obtained.
[0044] Comparative Example 1
[0045] This comparative example provides an asphalt composite additive that combines warm mixing and odor-reducing functions. The difference in its formulation compared to Example 1 is that the modified nano-activated carbon is replaced with an equal amount of unmodified nano-activated carbon (specific surface area 1300-1500 m²). 2 / g), the rest of the formulation and preparation method are the same as in Example 1.
[0046] Comparative Example 2
[0047] This comparative example provides an asphalt composite additive that combines warm mixing and deodorizing functions. The difference between its formulation and that of Example 1 is that, in the preparation of modified nano-activated carbon, cerium nitrate in the soluble metal salt used for loading is replaced with an equal amount of manganese nitrate.
[0048] Comparative Example 3
[0049] This comparative example provides an asphalt composite additive that combines warm mixing and deodorizing functions. The difference between its formulation and that of Example 1 is that, in the preparation of modified nano-activated carbon, cerium nitrate in the soluble metal salt used for loading is replaced with an equal amount of silver nitrate.
[0050] Test Example 1
[0051] The composite additives obtained in Examples 1-3 were added to the base asphalt at a mass ratio of 2% to form the experimental group. Meanwhile, to investigate the effect of the asphalt composite additive with both warm-mix and odor-neutralizing functions provided by this invention on the original properties of the base asphalt, base asphalt without any additives was used as the control group. The base asphalt from both the experimental and control groups was mixed with aggregates, and the conventional properties and viscosities at 110℃ and 135℃ of the different groups of asphalt were measured according to JTG E20-2011. The results are shown in Table 1.
[0052] Table 1
[0053]
[0054] Test Example 2
[0055] To verify the adsorption effect of the composite additive provided by this invention on flue gas, the smoke density of asphalt containing the composite additives of Examples 1-3 and Comparative Examples 1-3 was tested during the mixing process in accordance with the relevant provisions of the "Test Method for Smoke Density Rating of Building Materials Combustion or Decomposition" (GB / T 8627-2007). The test results are shown in Table 2.
[0056] Table 2
[0057]
[0058] Test Example 3
[0059] To verify the deodorizing effect of the composite additive provided by the present invention, the removal effect of harmful gases on asphalt (experimental group) and control group asphalt with the composite additives of Examples 1-3 and Comparative Examples 1-3 was tested: the asphalt samples to be tested were placed in a closed environment and heated to 120-130℃, and six gas samples were collected in the chamber. Two samples were collected as a group, and the concentrations of hydrogen sulfide, benzo[a]pyrene and VOCs were tested. The removal efficiency of harmful gases was calculated by comparing the concentrations of the experimental group and the control group. The results are shown in Table 3.
[0060] Table 3
[0061]
[0062] The above description is merely a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. An asphalt composite additive that combines warm mixing and odor-reducing functions, characterized in that, By weight, it comprises: 50-60 parts of polyethylene, 30-45 parts of polyvinyl acetate, 20-30 parts of maleic anhydride-grafted polyethylene, 35-50 parts of modified nano-activated carbon, and 15-25 parts of calcium stearate; the modified nano-activated carbon is loaded with metal oxides and silane coupling agents, wherein the metal oxides are a mixture of copper oxide, manganese oxide and cerium oxide.
2. The asphalt composite additive with both warm mixing and odor-reducing functions as described in claim 1, characterized in that, The loading rate of the metal oxide on the surface of the nano-activated carbon is 20%-28%.
3. The asphalt composite additive with both warm mixing and odor-reducing functions as described in claim 2, characterized in that, The specific surface area of the nano-activated carbon is 1000-2000 m². 2 / g.
4. The asphalt composite additive with both warm mixing and odor-reducing functions as described in claim 1, characterized in that, The method for preparing the modified nano-activated carbon is as follows: Nano-activated carbon is dispersed in an acidic solution and stirred at 70-80℃ for 3-4 hours to obtain an activated slurry; The pH of the activated slurry was adjusted to 7.5-9, and soluble metal salts of copper, manganese and cerium were added. The mixture was stirred and reacted at 60-70℃ under ultrasonic conditions for 10-12 hours. After solid-liquid separation, the obtained solid was washed and calcined at 400-450℃ under inert conditions for 1-2 hours to obtain metallized nano-activated carbon. The metallized nano-activated carbon was dispersed in an alcohol solution containing a silane coupling agent and stirred at 40-50°C for 4-6 hours. After solid-liquid separation, the mixture was dried to obtain the modified nano-activated carbon.
5. The asphalt composite additive with both warm mixing and odor-reducing functions as described in claim 4, characterized in that, The amount of the soluble metal salt added is 40%-80% of the mass of the nano-activated carbon.
6. The asphalt composite additive with both warm mixing and odor-reducing functions as described in claim 5, characterized in that, The soluble metal salts of copper, manganese and cerium are the corresponding nitrates or chlorides.
7. The asphalt composite additive with both warm mixing and odor-reducing functions as described in claim 6, characterized in that, In the soluble metal salts of copper, manganese and cerium, the mass ratio of copper salt, manganese salt and cerium salt is 1:2-3:0.5-0.8 respectively.
8. The preparation method of the asphalt composite additive with warm mixing and deodorizing functions according to any one of claims 1-7, characterized in that the step include: The modified nano-activated carbon, a portion of maleic anhydride-grafted polyethylene, and a portion of calcium stearate were added to a high-speed mixer in proportion and mixed for 5-10 minutes to obtain a premix. The polyethylene, polyvinyl acetate, the balance of maleic anhydride-grafted polyethylene, and the balance of calcium stearate are mixed together with the premix and then mixed in a high-speed mixer for 10-15 minutes to obtain the mixture. The mixture is sequentially heated and melted, then extruded and granulated to obtain the asphalt composite additive that combines warm mixing and odor removal functions.
9. The preparation method of the asphalt composite additive with both warm mixing and deodorizing functions as described in claim 8, characterized in that, The process of heating, melting, extruding, and granulating specifically involves heating the mixture to 160-180℃ in a twin-screw extruder for 3-5 minutes, setting the screw speed to 300-400 rpm, and then extruding and granulating.
10. A warm-mix asphalt, characterized in that, The asphalt composite additive comprising the warm-mix and odor-neutralizing functions as described in any one of claims 1-7, or the asphalt composite additive comprising the warm-mix and odor-neutralizing functions prepared according to the preparation method described in any one of claims 8-9.